THE ROLE OF CIVIL SOCIETY IN POLITICAL MODERNIZATION: PROBLEMS AND DIRECTIONS OF DEVELOPMENT - Marina Rybasova (Гуманитарные и юридические исследования)
The article deals with the problems of formation of civil society in the Russian Federation, the quantitative and qualitative growth of public organizations, strengthening of their role in socio-political development of the country. The author emphasizes the important role of cooperation between the state, business community, civil society and non-governmental organizations in solving social problems.